Quorum Quenching and Antimicrobial Activity of Goldenseal (Hydrastis canadensis) against Methicillin-Resistant Staphylococcus aureus (MRSA) - Cech, Nadja B.; Junio, Hiyas A.; Ackermann, Laynez W.; Kavanaugh, Jeffrey S.; Horswill, Alexander R. (Planta Medica, 2012)
The popular herbal remedy goldenseal (Hydrastis canadensis L.) is traditionally used to treat skin infections. With this study, we show activity of H. canadensis extracts in vitro against methicillin-resistant Staphylococcus aureus (MRSA). An extract from H. canadensis leaves demonstrated more potent antimicrobial activity than the alkaloid berberine alone (MICs of 75 µg/mL and 150 µg/mL, respectively). LC-MS detected alkaloids and efflux-pump inhibitory flavonoids in the extract, and the latter may explain the enhanced efficacy of the extract compared to berberine alone. We also show evidence of anti-virulence activity as a second mechanism by which H. canadensis acts against S. aureus. The H. canadensis leaf extract (but not the isolated alkaloids berberine, hydrastine, and canadine) demonstrated quorum quenching activity against several clinically relevant MRSA isolates (USA300 strains). Our data suggest that this occurs by attenuation of signal transduction through the AgrCA two-component system. Consistent with this observation, the extract inhibited toxin production by MRSA and prevented damage by MRSA to keratinocyte cells in vitro. Collectively, our results show that H. canadensis leaf extracts possess a mixture of constituents that act against MRSA via several different mechanisms. These findings lend support for the traditional application of crude H. canadensis extracts in the prevention of infection.
Keywords: Hydrastis canadensis; Ranunculaceae; quorum quenching; berberine; methicillin-resistant Staphylococcus aureus; anti-virulence